2014
DOI: 10.1007/s11060-014-1679-8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive improvement in meningioma patients after surgery: clinical relevance of computerized testing

Abstract: Cognitive dysfunction is common in patients with primary brain tumors, and may have a major impact on activities of daily living and on quality of life. This is the first prospective study that investigated the incidence and severity of cognitive dysfunction in meningioma patients before and after surgery, and the change in dysfunction over time, both at group and individual patient level. Sixty-eight meningioma patients were neuropsychologically tested one day before brain surgery. Sixty-two patients were fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 18 publications
1
68
0
4
Order By: Relevance
“…All patients provided written informed consent. There is considerable overlap between the patient sample of this study and four previously published studies …”
Section: Methodsmentioning
confidence: 95%
“…All patients provided written informed consent. There is considerable overlap between the patient sample of this study and four previously published studies …”
Section: Methodsmentioning
confidence: 95%
“…Other studies have reported significant cognitive impairment in meningioma patients either pre- or post- surgery [9, 10], although the average tumor size in both of these studies was much greater than the average size of tumor in our study. Those looking at patients both before and after surgery show mixed findings based on factors such as type of intervention, meningioma size, and patient characteristics [7, 8, 19, 20]. Previous authors have suggested the cognitive impairment could be due to mass effect, edema, and even extra-tumor factors such as seizures and anti-seizure medications.…”
Section: Discussionmentioning
confidence: 99%
“…Study participants with a primary diagnosis of central nervous system cancer were the most likely to report PCD (81 %). This percentage is likely high due to direct tumor impact in survivors of primary brain tumors [31, 32], and may also be due to treatment-related factors such as the known side effects of bevacizumab and anti-epileptic drugs that are normally prescribed for CNS cancer patients [33, 34]. However, PCD was widely reported among survivors of all cancer types with about half of the study participants with breast, lymphoma, colorectal, and head and neck cancers reporting PCD (44.2–57.6 %, see Fig.…”
Section: Discussionmentioning
confidence: 99%